2020
DOI: 10.1007/s00415-020-10313-8
|View full text |Cite
|
Sign up to set email alerts
|

Critical illness-associated cerebral microbleeds for patients with severe COVID-19: etiologic hypotheses

Abstract: Background and purpose During the COVID-19 outbreak, the presence of extensive white matter microhemorrhages was detected by brain MRIs. The goal of this study was to investigate the origin of this atypical hemorrhagic complication. Methods Between March 17 and May 18, 2020, 80 patients with severe COVID-19 infections were admitted for acute respiratory distress syndrome to intensive care units at the University Hospitals of Strasbourg for whom a brain MRI for neurologic manifestations was performed. 19 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 25 publications
(32 reference statements)
2
44
0
Order By: Relevance
“… 4 Lersy et al found that CMBs in COVID-19 patients were significantly associated with high D-dimer levels. 15 These findings are consistent with our study, showing significantly higher D-dimer levels and SOFA scores in patients with neurological events vs. those without ( Table 3 ).…”
supporting
confidence: 93%
“… 4 Lersy et al found that CMBs in COVID-19 patients were significantly associated with high D-dimer levels. 15 These findings are consistent with our study, showing significantly higher D-dimer levels and SOFA scores in patients with neurological events vs. those without ( Table 3 ).…”
supporting
confidence: 93%
“…The pattern of the microbleeds distribution is unspecific in patients with COVID-19 encephalopathy and does not follow those reported in patients with amyloid angiopathy [19], in patients with hypertension [20] or in patients with critical illnesses [21]. Hypoxemia and high concentration of uremic toxins leading to BBB dysfunction in patients with COVID-19 have been suggested as the main mechanism leading to cerebral microbleeds in COVID-19 and may explain this atypical pattern of distribution and this increased prevalence of microbleeds [22].…”
Section: Discussionmentioning
confidence: 85%
“…26 To address this, Lersy et al compared the clinical characteristics of patients with COVID-19 that had either (a) a normal brain MRI or (b) extensive white matter microhemorrhages. 27 The authors found that the patients with intracranial microhemorrhages were intubated for a longer period of time on average (24 days compared to 8 days, respectively; P¼0.0002), required higher levels of fractional inspired oxygen (FiO 2 ) (100% vs. 75%, respectively; P ¼ 0.03), and were more likely to be on ECMO (five patients versus no patients, respectively; P¼0.04). These findings would seem to indicate that at least some of the observed abnormalities are related to microhemorrhages of critical illness, rather than necessarily being specific to COVID-19.…”
Section: Discussionmentioning
confidence: 99%